"Voices of the broken body." The resumption of non-professional female players' sports careers after anterior cruciate ligament injury. The female player's dilemma: is she willing to run the risk? - Thing, L. F. (Scandinavian Journal of Medicine & Science in Sports, 2006)
The article takes as its starting point the lived experiences of female sports patients in rehabilitation. The research data are semi-structured qualitative interviews (N=17) with non-professional female players as patients, having anterior cruciate ligament injuries (ACL-injuries). Injury narratives have been conducted, with a focus upon how female handball players managed the injured situation. Ethnographic research was taken in a private physiotherapy clinic over a period of more than 1 ½ years. The narratives show the impact of risk management - the individual coping strategy of the players. The handball her-player has choices to make regarding the resumption of the career. The options and possibilities of playing or not playing after an ACL-injury are connected to the trust in the capacity of the body. The concept of bodily risk reflexive coping strategy is constructed to understand the question of the resumption of the career. The individualistic self-care management indicates a manageable body with a desire to act as worthy of being a full part of the sporting society. This strategy is adding to the sense of accomplishment and to the continuing development of self-identity. The study shows that there is a need for guidance in the injury process. Playing is connected with pleasurable feelings and excitements, but the her-player does care for the bodily self and her risk assessment is so far not a "misuse" or a consumption of sports medicine in the name of sporting achievements